A Relationship Between ITCZ Organization and Subtropical Humidity. Issue 16 (21st August 2020) - Hohenegger, Cathy; Jakob, Christian
Abstract: Motivated by the results of idealized studies on the self‐aggregation of convection, we investigate a potential relationship between the degree of organization of the Intertropical Convergence Zone (ITCZ) and humidity based on reanalysis data. We focus on the Atlantic ITCZ and use the number of long convergence lines occurring per month to define the degree of organization. The latter shows a weak enhancement during June to August (JJA) and a large interannual variability. On an interannual time scale and particularly during JJA, a relationship exists between organization and humidity: Years with more organized ITCZs are associated with a moister ITCZ region and drier subtropics. Even though we cannot demonstrate any causality and cannot rule out the presence of another agent, we show that these moisture anomalies are not incompatible with an effect of organization. We also note that the annual cycle in sea surface temperature (SST) gradient may contribute to the intra‐annual variability in organization. Plain Language Summary: The large‐scale organization of individual convective cells into a coherent structure over the tropics, the Intertropical Convergence Zone (ITCZ), is an easily recognizable feature of satellite imagery. At times, the ITCZ appears well organized, forming a long line, whereas at other times, it appears much more scattered and made of disconnected convective clusters. We investigate the hypothesis, derived from previous idealized studies, that a relationship exists between organization and atmospheric humidity. We quantify organization by counting the number of times per month the ITCZ is organized in a long line. The study shows for the first time that, indeed, a relationship exists between the large‐scale degree of convective organization and humidity in the real world: Years with a more organized ITCZ are associated with drier subtropics and a moister ITCZ region. Given the importance of subtropical humidity for the energy budget of the climate system, our results ask for more studies investigating this relationship and its causality. Key Points: The large‐scale organization of the Atlantic ITCZ is quantified using a 35‐year data set of convergence lines Relationships derived from reanalysis data between convective organization and humidity are consistent with results from idealized studies Years with a more organized ITCZ structure are associated with drier conditions in the subtropics